An open-label randomized trial of intramuscular olanzapine versus oral clonidine for symptomatic treatment of opioid withdrawal in the emergency department*. (3rd August 2019) - Klein, Lauren R.; Cole, Jon B.; Driver, Brian E.; Miner, James R.; Laes, JoAn R.; Fagerstrom, Erik; L. Martel, Marc
Abstract: Background: Patients with opioid withdrawal often present to the Emergency Department (ED), but many EDs do not have the infrastructure in place to initiate treatment with opioid agonists (methadone or buprenorphine). Therefore, ED management often entails symptomatic control. The purpose of this study was to compare olanzapine to clonidine for the treatment of opioid withdrawal symptoms. Methods: This was a prospective, randomized clinical trial comparing 10 mg of IM olanzapine to 0.3 mg of oral clonidine for symptoms of opioid withdrawal. Adult (18 years and older) ED patients reporting a history of opioid use and symptoms consistent with withdrawal were eligible. Patients were excluded if they had already received treatment during the ED encounter, were pregnant, incarcerated, or unable to provide consent. Patients were randomized 1:1 to receive olanzapine or clonidine for their initial treatment. A baseline Clinical Opiate Withdrawal Scale (COWS) score was calculated. After 30 min, the patient could receive any additional treatment at the ED physician's discretion. The primary outcome was need for additional medication (rescue) within 1 h of study medication administration. Secondary outcomes included change in COWS score and adverse reactions. Results: We enrolled 63 patients (33 olanzapine, 30 clonidine). Demographic characteristics were similar for both groups (median age 45, range 21–67, 54% male) as well as baseline COWS score (median score 11). The median time since last opiate use was 48 h for both groups (range 4–116). Rescue was given within 1 h for olanzapine for 9 (27%) patients and for clonidine in 19 (63%) patients (difference 36%, 95% CI 13–59%). Decrease in COWS score at 1 h was 8.3 for olanzapine and 5.1 for clonidine (difference 3.2, 95% CI 0.3–6). Adverse events were uncommon: akathisia (1, olanzapine), hypotension (2, clonidine), respiratory depression (0). Conclusions: Treatment of opioid withdrawal symptoms with 10 mg of IM olanzapine results in a lower incidence of rescue medication administration and improved symptoms (COWS score) compared to 0.3 mg of oral clonidine.